Microencapsulation of Phycocyanin from Spirulina platensis by Freeze-Drying: Optimization of Maltodextrin–Soy Protein Matrices for Enhanced Stability and Antioxidant Functionality - Dian Marlina; Ryan Werytama Saputra; Takad Bagas Aji Prasetyo; Hery Muhamad Ansory; Siti Aisiyah; Desi Purwaningsih (Advance Sustainable Science Engineering and Technology, 2026)
Phycocyanin, a natural blue pigment from Spirulina platensis, exhibits strong antioxidant activity but is highly unstable under light, heat, and pH variations, limiting its practical applications. This experimental study addresses the lack of systematic optimization data on maltodextrin–soy protein isolate (SPI) wall matrices for phycocyanin microencapsulation via freeze-drying. Phycocyanin was extracted using phosphate buffer and encapsulated at different maltodextrin:SPI ratios (9:1, 8:2, and 7:3). Each formulation was analyzed in triplicate (n = 3) for encapsulation efficiency (EE), phycocyanin retention, moisture content, particle size, and antioxidant activity (DPPH assay). The 8:2 ratio exhibited the best performance with EE of 88.5%, phycocyanin content of 0.710 mg·mL⁻¹, and particle size of 70.2 µm. Moderate antioxidant activity was observed (IC₅₀ = 102.29 ppm). ANOVA confirmed that the polymer ratio significantly affected all parameters (p < 0.05). Overall, the optimized maltodextrin–SPI microcapsules enhanced the stability and antioxidant functionality of phycocyanin under laboratory conditions, supporting their potential application as bioactive ingredients in functional food and pharmaceutical formulations.